Peran Collaborative Governance dalam Pembangunan Desa di Desa Panda - Kamaluddin Kamaluddin; Taufik Irfadat; Sajratul Aditia Kamrila (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this study was to determine the form of collaboration between village institutions and the village government in carrying out the development of panda village, palibelo sub-district, bima district. With the research method, namely qualitative, the results of the research are that the development of panda village also collaborates and involves BPD, youth organizations, village youth, religious / community leaders. plays a very important and strategic role in national and regional development because it contains elements of equitable development and its effects directly touch the interests of rural communities and in the form of improving welfare. In Village Development, the village government as a subsystem of the Indonesian government system allows the village to have the power, duties and obligations to regulate and manage the interests of its own community, the fulfillment of the authority of duties and obligations in the administration of village government and development requires a village-level source of income. The role of the Panda Village Government in the implementation of village development includes the supply of funds. This means distributing funds from the APBDes (Village Revenue and Expenditure Budget), district government sharing funds, and social assistance program funds such as PNPM to be handed over to the community through the development implementation committee